"Pintu terlarang"; A disconcerting spatial interpretation of urban dystopia - Kristianto, Bayu (Wacana, Journal of the Humanities of Indonesia, 2012)
The main character of the film Pintu terlarang (The forbidden door), Gambir, attains success in the art world by making statues of pregnant women. Part of his creative process is to insert dead foetuses into the wombs of the statues. His troubled soul meets a written request for help by a child he encounters in various places. The journey to find the child leads him to a secret door, revealing a terrifying reality of a dehumanized world. The city, commonly characterized by a sense of vastness, is set in opposition to small, enclosed spaces where individuals converse with their utmost self. The questions explored are: What is the role of space in engendering urban dystopia? In what ways does the selection of different space settings help create a dehumanized world? I argue that urban dystopia is created when the inhabitants of a city return to enclosed spaces in an effort to find an existence. When individuals prefer enclosed spaces and fail to reconstruct existing meanings, tendencies toward dystopia will come forward and city life will degenerate.